Analysis of Market Reactions in Various Industry Sectors Before and After the Announcement of Indonesia's Exposure to the Covid-19 Outbreak - Riska Rosdiana (DINASTI RESEARCH, 2023)
This study aims to determine the effect of the announcement of the entry of COVID-19 in Indonesia on abnormal returns, trading volume activity and bid-ask spread in the Miscellaneous industry sector listed on the Indonesia Stock Exchange (IDX). The sampling technique used in this study was using the census sampling method and from this method data were obtained as many as 45 companies in the Miscellaneous industry. The method used in this study is an event study, where the event window in this study consists of 7 days before and 7 days after the announcement of the entry of COVID-19 in Indonesia. Hypothesis testing was carried out using the paired-sample t-test and the Wilcoxon signed rank test. The results showed that there were significant differences in trading volume activity before and after the announcement of the entry of COVID-19 in Indonesia. However, there are no significant differences in abnormal returns before and after the announcement of the entry of COVID-19 in Indonesia.